POWER SHARING IN MEDICAL CONSULTATIONS - Junaid, Ayesha; Rafi, Muhammad Shaban; Khan, Najm Us Saqib; Khan, Junaid Sarfraz (Pakistan Armed Forces Medical Journal, 2020)
Objective: To examine the management of power by doctors in medical consultations. The power is defined here as a dialogic, egalitarian, and patient-centered. Study Design: Qualitative study. Place and Duration of Study: Out-patient departments of Mayo Hospital, Lahore, Pakistan, from Nov 2019 for two weeks. Methodology: The data were collected through in-depth interviews and observations from outpatient departments of Mayo Hospital. Bourdieu’s Social Practice Theory and Fairclough’s theory of Power and Language were used as a theoretical framework in the community of practice, for the interpretation of the qualitative data sets. Results: The interpretations of relational power by doctors and patients surface three themes: Power, Power and Solidarity, and Solidarity. Although power-sharing is the modern rhetoric, it is hardly conceptualized in the selected hospital. Conclusion: With a proliferation of patient-centered approach of the medical profession, power-sharing with patients might perpetuate dissatisfaction among the participants.